Education scholarship distribution management at Baznas Pohuwato - Dian Adi Perdana; Wahidah Suryani; Mirza Ghulam Achmad Adi Putra Umar; Muhammad Thahir (Journal of Islamic Economics Management and Business (JIEMB), 2022)
Baznas is declared a non-structural government institution that manages educational scholarship assistance for underprivileged children because education is a vital need for every comprehensive person, starting from the mindset, belief, and attitude of life that leads to quality of life. The purpose of this study was to examine the management of the distribution of educational scholarships at Baznas Pohuwato and to examine the obstacles in the distribution of academic scholarships at Baznas Pohuwato. This research is a qualitative descriptive method to answer questions about existing phenomenaâ€”data collection techniques through observation, interviews and documentation from primary and secondary data sources. The data obtained is then processed to produce conclusions from the phenomena found. The results of this study are the scholarship program at Baznas Pohuwato to improve achievement and educate the nation's children with a budget that will be allocated according to the expected student targets by analyzing the circumstances and needs of students. Baznas hopes that scholarship recipients can convey and introduce this program to other communities, and the community will be aware of the obligation to pay ZIS through Pohuwato to manage the funds collected. The Baznas Pohuwato can carry out routine socialization to people experiencing poverty so that the community will be aware of the activities and programs managed by the National Amil ZakÄt Â Agency (BAZNAS), especially the scholarship assistance program for poor children at all levels of education. In distributing scholarship assistance, the National Amil ZakÄt Agency (BAZNAS) would pay attention to the timeliness of scholarship distribution so that the waiting time for recipients is not too long.